Exploring the role of alignability effects in promoting uptake of energy-efficient technologies. - Becki Hafner (Journal of Experimental Psychology: Applied, 2020)
The current research applies decision-making theory to the problem of increasing uptake of energy-efficient technologies, where uptake is currently slower than one might predict following rational choice models. We explore the role of alignability effects on consumers’ preference for standard versus energy-efficient technologies. Previous research has found that attentional weight given to alignable or nonalignable features varies depending on the decision context, including between-alternative heterogeneity. In a hypothetical choice task, subjects were presented with a choice between similar (boiler vs. boiler) versus dissimilar (boiler vs. heat pump) home heating technologies, each described by a list of alignable and nonalignable attributes. We found a preference for alignability when options were similar; an effect mediated by an increased tendency to infer missing information is the same. No effects of alignability on preference were found when options differed. We draw theoretical and applied implications for (a) the role of alignability effects in contributing to the energy efficiency gap and (b) the type of information structure best suited for the promotion of energy-efficient technologies in future marketing campaigns.